A Web-Based Industrial Training Management System: A Case Study of the School Of Computing (Journal of Digital System Development, 2024)
Implementing an internship program is an integral part of an educational institution's academic operations, providing students with valuable experience in their chosen fields. However, effective program management ensures seamless collaboration between students and the university. This paper aims to develop and evaluate a prototype of a web-based industrial training management system tailored specifically for a university to address this need. Currently, the school uses online storage and an instant messaging application to manage student internships. Consequently, this implementation causes confusion, repeated questions, and redundant announcements that must be organised systematically. This development focuses on managing documentation, announcements, and communication among students and school members. The project employs a Rapid Application Development methodology to streamline the entire process from initiation to completion. The findings show high satisfaction with the system’s usefulness, ease of use, and learning in improving the management of industrial training processes. In conclusion, the resulting prototype demonstrates the potential benefits, including improved accessibility, streamlined internship management processes, and efficiency within the university.